2015
DOI: 10.1016/j.annepidem.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Social place as a location of potential core transmitters—implications for the targeted control of sexually transmitted disease transmission in urban areas

Abstract: Purpose Places are an important determinant of risk for sexually transmitted infection (STI) acquisition and transmission. We sought to identify social places that are critical for targeted STI control activities. The objective of this study was to determine whether sex partner meeting places characterized by drug markets, sex markets and separately, drug and/or sex markets were more likely to have potential core transmitters as compared to other sex partner meeting places in one urban setting. Methods In 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…A more focused or targeted control method that utilizes “venue analysis” to locate key social venues (bars, clubs, etc) where high-risk sexual behavior is prominent could be an effective intervention tool for public health; both for inducing and sustaining behavioral change as well as opportunities for testing and treating STIs. 60,61 Identifying locations such as these is important, as “place” is closely intertwined with social/sexual networks and ultimately impacts human behavior. 61 In a study by Jennings et al, 61 it was found that drug and sex market venues were more likely to be visited by core transmitters than other social venues.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more focused or targeted control method that utilizes “venue analysis” to locate key social venues (bars, clubs, etc) where high-risk sexual behavior is prominent could be an effective intervention tool for public health; both for inducing and sustaining behavioral change as well as opportunities for testing and treating STIs. 60,61 Identifying locations such as these is important, as “place” is closely intertwined with social/sexual networks and ultimately impacts human behavior. 61 In a study by Jennings et al, 61 it was found that drug and sex market venues were more likely to be visited by core transmitters than other social venues.…”
Section: Recommendationsmentioning
confidence: 99%
“…60,61 Identifying locations such as these is important, as “place” is closely intertwined with social/sexual networks and ultimately impacts human behavior. 61 In a study by Jennings et al, 61 it was found that drug and sex market venues were more likely to be visited by core transmitters than other social venues. In addition, in a study by Fujimoto et al, 62 a similar connection was made among young, black MSM; syphilis cases were associated with a higher number of social venues attended, while HIV-syphilis coinfected cases were more likely to be associated with social network.…”
Section: Recommendationsmentioning
confidence: 99%
“…101 Other studies use more specific constructs, such as neighbourhood-level characteristics and HIV and STI. [102][103][104][105] For example, one study of sex partner meeting places showed that core transmitters were more likely to be found in venues with drug and sex 'market' activity. 102 Another study examining social support and cohesion among city neighbourhoods in the US found that informal social control at the neighbourhood level was protective for young women, but unrelated for young men; in contrast, individual social support was associated with a large increase in the odds of having an STI, but only for young men.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…[102][103][104][105] For example, one study of sex partner meeting places showed that core transmitters were more likely to be found in venues with drug and sex 'market' activity. 102 Another study examining social support and cohesion among city neighbourhoods in the US found that informal social control at the neighbourhood level was protective for young women, but unrelated for young men; in contrast, individual social support was associated with a large increase in the odds of having an STI, but only for young men. 103 The authors of that study speculated that these counterintuitive findings may be based on the connections of young men with social support (e.g.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…1725 For example, prior literature demonstrates associations of exposure to drug market activity, alcohol outlets, violence, and incarceration rates with selecting sexual network partners who are infected with HIV/STIs or vulnerable to acquiring HIV/STIs. 18,2025 …”
Section: Introductionmentioning
confidence: 99%